Impact of a Service Provider Incentive Payment Scheme on Quality of Reproductive and Child-health Services in Egypt - Huntington, Dale; Zaky, Hassan HM; Shawky, Sherine; Fattah, Faten Abdel; El-Hadary, Eman (Journal of Health, Population and Nutrition, 2010)
A case-control, quasi-experimental study was designed (post-test only) to investigate the effect of a performance- based incentive payment scheme on behaviours of public-sector service providers in delivering a basic package of maternal and child-health services in Egyptian primary healthcare units. The results showed significant improvements in the quality of family-planning, antenatal care, and child-care services as reported by women seen in clinics where the incentive payment scheme was in operation as measured by various indicators, including both technical and inter-personal communication content. An analysis of characteristics of the service providers and clients found no significant or meaningful differences between the study groups, and the facilities of both the study groups were essentially the same. Some findings are suggestive of other influences on behaviours of the service providers not captured by the data-collection instruments of the study. Subsequent to this study, the payment scheme has been rolled out to other districts in Egypt. Key words: Performance payments; Child Health; Reproductive health; Impact studies; Quality of care; Case-control studies; Health services; Egypt DOI: 10.3329/jhpn.v28i3.5556 J HEALTH POPUL NUTR 2010 Jun;28(3):273-280